A review on effects of nitriding of AISI409 ferritic stainless steel. (2020) - Tadepalli, Lakshmi Deepak; Gosala, Ananda Mithra; Kondamuru, Lokesh; Bairi, Sai Chandra; Subbiah, Ram; Singh, Swadesh Kumar
Abstract: A review is presented on the effects of Nitriding of AISI 409 Ferritic Stainless Steel with a composition of C-0.08%, Mn-1%, Si-1%, Cr-10.5–11.75%, Ni-0.5%, P-0.045%, S-0.045%, Ti-0.75%, Fe-remaining. AISI409 Ferritic Stainless Steel is extensively used for many industrial and automotive applications. It has excellent atmospheric corrosion resistance which is superior to any of the martensitic steels. However, it has low wear resistance, hardness and toughness which ultimately reduces its applications. To improve these mechanical properties, surface treatment using Nitriding of AISI409 is done and it eventually broadens the areas of applications of these steels.